2011
DOI: 10.1177/0022219411413544
|View full text |Cite
|
Sign up to set email alerts
|

RAN and Double-Deficit Theory

Abstract: Lervag and Hulme's neuro-developmental theory and Wolf and Bowers's double-deficit hypothesis were examined in this longitudinal study. A total of 130 children were tested in preschool and followed through fifth grade, when 84 remained in the study. During preschool and kindergarten the participants were given tests of end-sound discrimination (phonological awareness; PA) and the rapid naming of objects (rapid automatic naming; RAN) and were placed into the four groupings of the double-deficit hypothesis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
1
18
0
6
Order By: Relevance
“…This assumption is supported by the results of this study, since the double-deficit children in the control group performed about one to two standard deviations below the performance of the children in the no-deficit and the single-deficit groups. This result mostly agrees with the investigations of Kirby et al (2003), Cronin (2013) and Torppa et al (2013).…”
Section: Discussionsupporting
confidence: 93%
“…This assumption is supported by the results of this study, since the double-deficit children in the control group performed about one to two standard deviations below the performance of the children in the no-deficit and the single-deficit groups. This result mostly agrees with the investigations of Kirby et al (2003), Cronin (2013) and Torppa et al (2013).…”
Section: Discussionsupporting
confidence: 93%
“…25 We used the Comprehensive Test of Phonological Processing (CTOPP) to assess skills that support reading decoding, speed, and fluency. [26][27][28][29] Two CTOPP composite scores were used: phonological awareness (ie, sound blending, elision) and rapid naming (ie, verbal retrieval of symbols). All of these tests have demonstrated good to excellent reliability and validity.…”
Section: Methodsmentioning
confidence: 99%
“…All of these tests have demonstrated good to excellent reliability and validity. [23][24][25][26][27][28][29] Age-based standardized scores with a mean of 100 and SD of 15 were used for all measures.…”
Section: Methodsmentioning
confidence: 99%
“…There are also contradictory findings on the role of single-deficit subgroups based on DDH: even though a group with double-deficit has often been the poorest in most literacy skills, not all studies have found significant differences between single-deficit groups in reading skills (e.g. Cronin, 2013;, see also for review).…”
Section: The Double-deficit Hypothesismentioning
confidence: 99%
“…It is assumed that the most severe reading disabilities are manifested in the double-deficit group, which reflects the additive nature of naming speed deficit and phonological deficit. A number of studies have been able to replicate and confirm the DDH in several languages and in samples with variety of reading skills (for reviews, see Georgiou & Parrila, 2013;, and for the most recent results, see Cronin, 2013;Torppa et al, 2012Torppa et al, 2013). Several results support the independent role of RAN as a predictor of reading disabilities.…”
mentioning
confidence: 91%